2006
DOI: 10.1249/01.mss.0000228936.78916.23
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Nitric Oxide and Bubble Formation in Divers

Abstract: The present study demonstrates that intake of a short-lasting NO donor reduces bubble formation following decompression after different dives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 16 publications
4
43
0
Order By: Relevance
“…Infusinġ NO donor drugs reduces injury in decompressed animals and decreases the number of intravascular bubbles in both animals and humans (6,23,34,39). Given the varied effects of˙NO these findings are not necessarily contradictory to observations in our study.…”
Section: Discussionsupporting
confidence: 50%
“…Infusinġ NO donor drugs reduces injury in decompressed animals and decreases the number of intravascular bubbles in both animals and humans (6,23,34,39). Given the varied effects of˙NO these findings are not necessarily contradictory to observations in our study.…”
Section: Discussionsupporting
confidence: 50%
“…Many research efforts have focused on the role of nitric oxide as a marker of the general " health " of the endothelium and as a mediator of the hydrophilic/hydrophobic properties of the endothelial wall ( 8,13,23,38 ). Furthermore, the respiration of oxygen before the dive ( 9 ), or again, a short hyperbaric exposure ( 19,24 ), seems to be capable of reducing the nitrogen content of these nuclei and exerting a protective role on postdive VGE.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our vibration sessions did not result in a signifi cant modifi cation of the endothelial reactivity, as indicated by the FMD measurements, we do not think NO production or vessel wall reactivity was signifi cantly altered in our study subjects. Previously it has been shown that administration of nitroglycerin prior to a dive may reduce bubble formation after the dive and the use of short-acting NO donors has been suggested as a protective measure ( 13 ). Whether the combination of NO donors and low-intensity vibration would lead to an even greater reduction in VGE remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) might be involved in the prevention of bubble formation, the central goal in decompression procedures. The intake of an NO donor reduces bubble formation following decompression in divers [315].…”
Section: Treatmentmentioning
confidence: 99%